Integrating CSR with Employer Branding Initiatives: Proposing a Model - Kumar, Prabhat; Rose, Anthony; Jain, Shikha; Pole, Makarand; Bhatt, Vimal (The journal of contemporary issues in business and government, 2021)
Building a strong reputation is one of the highest priorities for organizations. ‘Reputation’, synonymous to the organization’s ‘brand’, silently inspires perceptions of those who view the organization holistically, apart from its products, activities and interactions. Organizations are also looked upon as a brand based on how they are viewed as an employer, often termed as ‘employer brand’. The concept is best understood as the initiatives and actions taken in positioning the organization as a credible employer in the hearts and minds of the former, current and potential future employees. The employer branding initiatives should aim to inform the stakeholders about the potential benefits the workplace offers. It should also lead to transmitting trust among future employees in an attempt to reduce the perceived risk associated with future employment. One of the ways to ensure effective communication with relevant stakeholders is through the integration of Corporate Social Responsibility in the employer branding activities. This shall lead to strengthening its stand as a responsible workplace, which is a key to attract talented job aspirants. This paper focuses on leveraging the CSR induced benefits to and integration with employer branding initiatives of the organization. This strategy will ultimately help the firm in establishing and strengthening its image as a trustworthy and fair employer may serve as a differentiator.